Comparison of EV-free fraction, EVs, and total secretome of amniotic mesenchymal stromal cells for their immunomodulatory potential: a translational perspective - Papait, Andrea; Ragni, Enrico; Cargnoni, Anna; Vertua, Elsa; Romele, Pietro; Masserdotti, Alice; Perucca Orfei, Carlotta; Signoroni, Patrizia Bonassi; Magatti, Marta; Silini, Antonietta R.; De Girolamo, Laura; Parolini, Ornella (Frontiers in Immunology, 2022)
Amniotic mesenchymal stromal cells (hAMSC) have unique immunomodulatory properties demonstrated in vitro and in vivo in various diseases in which the dysregulated immune system plays a major role. It is well known that the immunomodulatory and pro-regenerative effects of MSC, among which hAMSC, lie in the bioactive factors they secrete and in their paracrine activity. The mix of these factors (i.e. secretome) can be either freely-secreted or conveyed by extracellular vesicles (EV), thus identifying two components in the cell secretome: EV-free and EV fractions. This study aimed to discern the relative impact of the individual components on the immunomodulatory action of the hAMSC secretome in order to obtain useful information for implementing future therapeutic approaches using immunomodulatory therapies based on the MSC secretome. To this aim, we isolated EVs from the hAMSC secretome (hAMSC-CM) by ultracentrifugation and validated the vesicular product according to the International Society for Extracellular Vesicles (ISEV) criteria. EVs were re-diluted in serum-free medium to maintain the EV concentration initially present in the original CM. We compared the effects of the EV-free and EV fractions with those exerted by hAMSC-CM in toto on the activation and differentiation of immune cell sub-populations belonging to both the innate and adaptive immune systems. We observed that the EV-free fraction, similar to hAMSC-CM in toto: a) decreases the proliferation of activated peripheral blood mononuclear cells (PBMC), b) reduces the polarization of T cells toward inflammatory Th subsets and induces the induction of regulatory T cells; c) affects monocyte polarization to antigen presenting cells fostering the acquisition of anti-inflammatory macrophage (M2) markers; d) reduces the activation of B lymphocytes and their maturation to plasma cells. We observed instead that all investigated EV fractions, when used in the original concentrations, failed to exert any immunomodulatory effect, even though we show that EVs are internalized by various immune cells within PBMC. These findings suggest that the active component able to induce immune regulation, tested at original concentrations, of the hAMSC secretome resides in factors not conveyed in EVs. However, EVs isolated from hAMSC could exert actions on other cell types, as reported by others.